Аналіз закономірностей ультрафільтрації при освітленні соків та визначення напрямів експериментальних досліджень - Дейниченко, Григорій Вікторович; Дмитревський, Дмитро В’ячеславович; Гончар, Дмитро Олександрович; Лавренюк, Владислав Вікторович; Deynichenko, Gregoriy; Dmytrevskyi, Dmytro; Honchar, Dmytro; Lavreniuk, Vladyslav (Запоріжжя : Видавничий дім «Гельветика», 2026)
UA: У статті проаналізовано закономірності ультрафільтрації при освітленні фруктових соків з урахуванням впливу селективності мембран, трансмембранного тиску, гідродинамічних умов та фізико-хімічних властивостей сировини на ефективність процесу. Показано, що основними факторами зниження продуктивності є концентраційна поляризація та мембранне забруднення, механізми яких мають багатофакторний характер. Узагальнено сучасні наукові підходи до моделювання ультрафільтрації та оптимізації технологічних режимів. Обґрунтовано напрями подальших експериментальних досліджень, спрямованих на підвищення стабільності процесу та якості освітленого соку. Отримані результати можуть бути використані для удосконалення мембранних технологій у харчовій промисловості та розроблення раціональних режимів промислової ультрафільтрації. /// EN: The article is devoted to the analysis of ultrafiltration regularities in the clarification of fruit juices with special attention to the influence of membrane selectivity, transmembrane pressure, hydrodynamic conditions and physicochemical properties of raw materials on process efficiency. Ultrafiltration is considered one of the most promising membrane technologies for juice clarification, enabling the removal of colloidal particles, pectic substances and high-molecular compounds while preserving valuable low-molecular components. However, practical implementation of the process is complicated by phenomena of concentration polarization and membrane fouling, which lead to a gradual decrease in permeate flux and changes in membrane selectivity. The study summarizes modern scientific approaches to describing mass transfer mechanisms and modeling ultrafiltration processes. It is shown that the formation of a polarization layer near the membrane surface creates additional resistance to mass transfer, and its thickness depends on hydrodynamic conditions and the composition of the juice. High concentrations of pectin and protein-polysaccharide complexes promote the formation of gel-like structures that intensify fouling and reduce productivity. Transmembrane pressure has a nonlinear effect on permeate flux: an initial increase in pressure enhances productivity, whereas further growth leads to compaction of the fouling layer and stabilization or even reduction of the flux. The influence of temperature, tangential flow velocity and membrane material properties on process stability is also considered. The necessity of combining experimental studies with mathematical modeling is substantiated to predict process behavior and determine optimal operating regimes. Directions for further research include quantitative evaluation of the impact of individual technological parameters, development of adaptive models that account for the multifactor nature of ultrafiltration, and experimental validation of optimal operating conditions. The obtained results can be applied to improve membrane technologies in the food industry, increase the efficiency of juice clarification and ensure stable product quality in industrial production.
Analysis of ultrafiltration patterns during juice illumination and determination of directions for experimental research
Keywords: ультрафільтрація; освітлення соків; мембранні процеси; фруктові соки; селективність мембран; трансмембранний тиск; продуктивність мембрани; мембранне забруднення; гідродинамічні умови; технологічні параметри; ultrafiltration; juice clarification; membrane processes; fruit juices; membrane selectivity; transmembrane pressure; membrane performance; membrane fouling; hydrodynamic conditions; technological parameters